Тысяча версий меня: [повесть : для среднего школьного возраста] / Веста Васягина ; художник Мария Колкер - Васягина Веста Анатольевна (Чит_code, 2023)
Экземпляры: Д. О. (20240723) / Инвентарный номер: 50362 / Цена: 264.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: В 20 / ББК: 84(2=411.2)6-4